Effect Of Fortivation Calcium-Rich Foodstuffs With Different Concentrations on the Organoleptic Quality of Ikan Tuna Kering Kayu Canned (Agrikan Jurnal Agribisnis Perikanan, 2021)
Research began from the preparatory stage, the manufacture of fortivation materials, namely tuna bone meal and anchovies, the manufacture of processed products dried tuna wood canned tuna, organoleptic tests and statistical analysis. Fortivation is carried out as many as five treatments, namely without fortivikasi or 0 % (A0), fortivikasi tuna bone meal 3 % (B1), tuna bone meal 6% (B2), anchovies 3% (C1), anchovies flour 6 % (C2). Fortivikasi canned wood dried tuna using bone meal tuna and anchovies with different concentrations, does not have a significant different influence on the quality of appearance, smell, taste and texture on the treatment of B1 and C1 additions of 3% of the total weight of the product with an average value of 8.4 and 8.3 respectively. While in addition to 6% B2 and C2 treatment, it gives a significant influence with an average value of 7.7 and 7.6 treatment, respectively.
Keywords: Fortivikasi; Canned Wood Dry Tuna; Organoleptic